Amazon alexa voice assistant on the base of raspberry pi as effective instrument for communication - Akintunde Adedamola Emmanuel (ХНУРЕ, 2019)
This paper describes and analyzes the development of Amazon Alexa voice assistant based on Raspberry Pi single-board computer. Also it describes the design of the voice assistant system, its system architecture with the hardware and software description which is required to keep the voice assistant up and running. As result in this paper will explained the implementation and testing of the voice assistant system working through its installation, launching, management and testing of the voice assistant system.